1998
DOI: 10.1128/aem.64.4.1298-1302.1998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Different Dextransucrase Activities Excreted in Glucose, Fructose, or Sucrose Medium by Leuconostoc mesenteroides NRRL B-1299

Abstract: When grown in glucose or fructose medium in the absence of sucrose,Leuconostoc mesenteroides NRRL B-1299 produces two distinct extracellular dextransucrases named glucose glucosyltransferase (GGT) and fructose glucosyltransferase (FGT). The production level of GGT and FGT is 10 to 20 times lower than that of the extracellular dextransucrase sucrose glucosyltransferase (SGT) produced on sucrose medium (traditional culture conditions). GGT and FGT were concentrated by ultrafiltration before sodium dodecyl sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 34 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…Dextran hydrolysis by endodextranase requires a minimum of six or seven non-substituted contiguously linked ␣-(1,6) glucose residues (Boune, Huston, & Weigel, 1962;Côté & Robyt, 1984;Richards & Streamer, 1978). Thus, the decision was made to make certain that L. mesenteroides FT045B was producing a real dextran with predominantly ␣-(1,6)-glucopyranosidic linkages within the main chains prior to carrying out the other characterization methods (Buchholz & Monsan, 2001;Dols et al, 1998;Seymour & Knapp, 1980). The mixture of oligosaccharides obtained from FT045B dextran hydrolysis were applied to TLC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dextran hydrolysis by endodextranase requires a minimum of six or seven non-substituted contiguously linked ␣-(1,6) glucose residues (Boune, Huston, & Weigel, 1962;Côté & Robyt, 1984;Richards & Streamer, 1978). Thus, the decision was made to make certain that L. mesenteroides FT045B was producing a real dextran with predominantly ␣-(1,6)-glucopyranosidic linkages within the main chains prior to carrying out the other characterization methods (Buchholz & Monsan, 2001;Dols et al, 1998;Seymour & Knapp, 1980). The mixture of oligosaccharides obtained from FT045B dextran hydrolysis were applied to TLC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dextran is an extracellular bacterial homopolysaccharide (Sidebotham, 1974;Monsan et al, 2001) , the main chain of which is composed of contiguous ␣-(1,6)-linked d-glucopyranose residues and branches, stemming mainly side-chains of ␣-(1,6) glucose units attached by ␣-(1,3) branch linkages to ␣-(1,6)linked chains (Buchholz & Monsan, 2001;Dols, Remaud-Simeon, Willemot, Vignon, & Monsan, 1998;Naessens, Cerdobbel, Soetaert, & Vandamme, 2005;Robyt, 1995;Seymour & Knapp, 1980). Some dextrans have ␣-(1,2) or ␣-(1,4) branch linkages, depending on the bacterial source.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse studies reported about the sucrose-inducible or pH-dependent release of dextransucrases in LAB [22,[33][34][35][36]. We recently observed that the dextransucrase of L. hordei is released into buffer supernatants efficiently in the presence of sucrose [24].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1950s, L. citreum NRRL B-1299 has received particular attention due to its ability to synthesize an unusual dextran containing up to 35% a-(1?2) linkages [26,[46][47][48][49]. Here we provide the assembled genome for this strain.…”
Section: Discussionmentioning
confidence: 99%